2018
DOI: 10.1093/treephys/tpy019
|View full text |Cite
|
Sign up to set email alerts
|

Heterosis in poplar involves phenotypic stability: cottonwood hybrids outperform their parental species at suboptimal temperatures

Abstract: Heterosis or hybrid vigor is common in hybrid poplars, and to investigate its occurrence and physiological basis we compared narrowleaf cottonwoods, Populus angustifolia James, prairie cottonwoods, Populus deltoides Bartr. ex Marsh, and their native intersectional hybrids, P. × acuminata Rydb., from Alberta, Canada. Clonal replicates from 10 separate trees from each taxon were raised in growth chambers at different temperatures (T). Growth was similarly vigorous across the taxa at 20 and 24 °C, and morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 52 publications
1
25
0
2
Order By: Relevance
“…Ex Marsh), along with their hybrids, which are referred to as lanceleaf cottonwoods (P. x acuminata Rydb. ; Gom & Rood, ; Rood et al, ; Zanewich, Pearce, & Rood, ). Some balsam poplar ( P. balsamifera L.) trees were also present.…”
Section: Methodsmentioning
confidence: 99%
“…Ex Marsh), along with their hybrids, which are referred to as lanceleaf cottonwoods (P. x acuminata Rydb. ; Gom & Rood, ; Rood et al, ; Zanewich, Pearce, & Rood, ). Some balsam poplar ( P. balsamifera L.) trees were also present.…”
Section: Methodsmentioning
confidence: 99%
“…Third, we tested whether genotype-by-environment (GxE) interactions are more prominent for inbred microbiomes than hybrid microbiomes, as they are for many plant traits (Lewis, 1954;Griffing & Zsiros, 1971;Blum, 2013;Zanewich et al , 2018) (but see (Li et al , 2018) ). We found that pairs of siblings from hybrid genotypes had less similar rhizosphere microbiomes than pairs of siblings from inbred genotypes, both within fields and between fields (Figure 6b).…”
Section: Patterns Of Microbiome Heritability In F 1 Crossesmentioning
confidence: 99%
“…According to genetic theory and empirical evidence, poplar hybrids are more likely to exhibit broad adaptability than pure natural species due to heterosis and increased heterozygosity (Lerner, 1954;Mitton and Grant, 1984;Gillespie and Turelli, 1989;Li and Wu, 1996;Wu, 1998;Zanewich et al, 2018). Recently, Zanewich et al (2018) provided corroborating physiological evidence for this hypothesis by showing that heterosis in poplar hybrids is tied to phenotypic stability or environmental adaptability, with heterozygosity providing metabolic diversity that leads to better performance than parental pure species, particularly under suboptimal conditions. This body of Cornell 10th…”
Section: Discussionmentioning
confidence: 99%